2016
DOI: 10.1089/cap.2015.0157
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation/Behavioral Intervention Clinical Trial: Long-Term Follow-Up of Outcomes in Congenital Hemiparesis

Abstract: Objective: The purpose of this study was to examine long-term outcomes of nonpharmacological intervention in children and adolescents with stroke utilizing repetitive transcranial magnetic stimulation (rTMS) to the primary motor cortex combined with constraint-induced movement therapy (CIMT) to improve motor function in the paretic hand. Outcome measures included function, satisfaction, and medical status review. Methods: Fourteen of the original 19 participants (74%) from our rTMS/CIMT clinical trial (real rT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A confidential family feedback form, filled out anonymously by the child and caregiver together, can provide helpful information (Appendix G in Supplementary Material). Additionally, formal follow-up at established time points after the study allows long-term assessment of participant status and interpretation of the potential longitudinal effects that NIBS may have ( 91 ).…”
Section: Study Design Considerationsmentioning
confidence: 99%
“…A confidential family feedback form, filled out anonymously by the child and caregiver together, can provide helpful information (Appendix G in Supplementary Material). Additionally, formal follow-up at established time points after the study allows long-term assessment of participant status and interpretation of the potential longitudinal effects that NIBS may have ( 91 ).…”
Section: Study Design Considerationsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We identified one study where the COPM goals were rescored at 21 to 57 months after an upper extremity intervention in children with hemiplegic cerebral palsy (CP); the study found that in 5 of 13 individuals, the COPM goals were no longer relevant. 28 A second study assessed the COPM 12 to 43 months after a rehabilitation intervention for whiplash and showed that the long-term impact of the rehabilitation programme was maintained. 29 Evaluating the capacity of the COPM to measure clinically 'important' change in individualized goals over longer durations would provide evidence for a tool that can be integrated into long-term research studies and clinical practice, a necessary and crucial step for assessing longterm impact of interventions for people with chronic conditions.…”
mentioning
confidence: 99%
“…It is typically used over a short timeframe, from 2 weeks to 1 year 11–27 . We identified one study where the COPM goals were rescored at 21 to 57 months after an upper extremity intervention in children with hemiplegic cerebral palsy (CP); the study found that in 5 of 13 individuals, the COPM goals were no longer relevant 28 . A second study assessed the COPM 12 to 43 months after a rehabilitation intervention for whiplash and showed that the long‐term impact of the rehabilitation programme was maintained 29 …”
mentioning
confidence: 99%
“…A total of seven children (4 females and 3 males) with congenital hemiparesis (mean age = 13 years; age range = 10---16 years) included in this study were enrolled in a transcranial direct current stimulation/constraint induced movement therapy study (ClinicalTrial.gov NCT02250092). 19 This report details baseline motor threshold and CSP duration. Informed consent and assent were obtained from all legal guardians and the children for study participation and for publication in this case series.…”
Section: Participantsmentioning
confidence: 99%
“…The EMG breakthrough activity has been reported in healthy adults. 5,18,19 However, no study, to our knowledge, has reported the EMG breakthrough activity in children with congenital hemiparesis.…”
Section: Introductionmentioning
confidence: 97%